Scaling better together―A Mural overview of scaling process of the livestock CRP - Dror, Iddo; Wu, Nicole; Kang'ethe, Edwin (CGIAR Research Program on Livestock, 2020)
A Mural created for the Livestock CRP review and planning meeting, outlining the scaling process, tools and approach to scaling of the CRP